Penalty payment for failure to decide on establishing the location of public purpose investment within the statutory deadline – selected issues - Rokicka-Murszewska, Karolina (Studia Iuridica Toruniensia, 2020)
The aim of this article is to analyze problems related to penalty payment for failure to decide on establishing the location of public purpose investment within the statutory deadline. In particular, an important issue in the context of this penalty concerned was its legal nature, determining the second problem – time-limit to dispose of a matter and the relationship between the penalty payment and guarantees for protection of the individual in the proceedings in matters involving decision on establishing the location of public purpose investment. The author signals possible problems that may occur in the procedure for the issue of a decision and imposition of a penalty payment. The conducted analysis became the basis for the de lege ferenda postulates in the Act on Spatial Planning and Land Development from 2003.